Influence of geotextile arrangement on seismic performance of mid-rise buildings subjected to MCE shaking. Issue 4 (August 2018) - Xu, Ruoshi; Fatahi, Behzad
Abstract: Geotextile layers make it possible to construct mid-rise buildings sitting on shallow foundations in unfavourable soil conditions; this study investigates how the arrangement of geotextiles affects the seismic performance of mid-rise buildings under Maximum Considered Earthquake (MCE) shaking. The geotextile arrangement considered here includes the stiffness (5000 kN/m – 12000 kN/m), the length with respect to width of the foundation (B) (1B – 4B), the number of geotextile layers (1 – 7 layers), and their spacing (250 mm – 1000 mm). FLAC3D is used for the numerical simulation and to carry out nonlinear dynamic analysis in the time domain, and an inelastic constitutive model is used to simulate the behaviour of the structure and the geotextile layers under seismic loads. Variations in the shear modulus of soil and the corresponding damping ratio with cyclic shear strain are considered using a hysteretic damping algorithm to model the reasonable dissipation of energy in the soil. The interface between the foundation and ground surface, including the material and geometrical nonlinearities, are used to capture any possible slide and uplift in the foundations. The results are presented with regard to the geotextile arrangement considered, and include the tensile force mobilised in the geotextile layers, the response spectra at the bedrock and ground surface, the shear force developed in the structure, the maximum rocking angle of the foundation, permanent foundation settlement, maximum lateral displacement and the maximum and residual inter-storey drifts. The results show that the geotextile layers close to the edges of the foundation sustained most of the stress induced by foundation rocking, and the geotextile arrangement has a significant influence on the seismic response of mid-rise buildings. Thus, to satisfy the seismic performance of buildings and to optimise the design of foundations reinforced with geotextiles, the stiffness, length, number and spacing of the geotextile layers should be designed with great care.